KEWENANGAN GUBERNUR DKI JAKARTA DALAM PENETAPAN UPAH MINIMUM PROVINSI BERDASARKAN PERMENAKER NO. 16 TAHUN 2024: Authority Governor Dki Jakarta In Establishing Provincial Minimum Wage Based On Manpower Minister Regulation Number 16 Of 2024 - Nasywa Tsuraya Pribadi; Andari Yurikosari (Reformasi Hukum Trisakti, 2026)
This study examines the role of the Governor of the Special Capital Region of Jakarta in determining the Provincial Minimum Wage (UMP) based on the Ministry of Manpower Regulation No. 16 of 2024. The background of this research is the wage policy dynamics in Jakarta, which often generate controversy, particularly the 2022 UMP determination by Governor Anies Baswedan, which caused tensions among the regional government, employers, and workers. The research problems focus on the UMP determination process by the governor and the governor’s role during the leadership periods of Joko Widodo, Basuki Tjahaja Purnama, and Anies Baswedan. The research method used is normative juridical, with a literature study approach on legislation and official documents, supported by interviews. The results show that the governor has a strategic authority in setting the UMP, integrating tripartite aspirations with local economic and social conditions. This process requires a balance between workers’ and employers’ interests, transparency, and compliance with national regulations. The study emphasizes the governor’s role as an accountable and fair decision-maker in setting the minimum wage and draws lessons from the 2022 case to strengthen governance mechanisms and UMP determination procedures in the future.